Solar to Thermal Energy Conversion Potential of Carbon Nanotubes Modified Copper Oxide Nanocomposite Thin Film Solar Selective Absorbers - Vinayagar K.; Karthick Kumar S.; Almansour A.I.; Sivaramasundaram K.; Selvi J.; Pugazhenthiran N.; Kandasamy M.; Muthuchelian K.; Suresh S. (John Wiley and Sons Inc, 2025)
Carbon nanotubes modified copper oxide nanocomposite (CNTs?CuO NC) selective absorbers were prepared through a sol-gel method by varying weight percentage of CNTs and coated on aluminum (Al) substrates using a dip coating technique to form thin films (TFs). The surface morphology of CNTs?CuO NC TF examined by scanning electron microscopy disclosed linear arrangement of CNTs?CuO NC TF with average particle diameter of 20030 nm. The X-ray diffractometer analysis of the CNTs?CuO NC TF revealed the presence of CuO in monoclinic crystal structure. Moreover, the X-ray diffractometer analysis disclosed good crystalline quality of the CNTs?CuO NC TF and average crystallite size of the CuO and CNTs?CuO NC TF was found to be 69.38 and 85.94 nm, respectively. The energy dispersive X-ray spectrum of CNTs?CuO NC TF ascertained the presence of Cu, O and C elements with atomic weight proportion of 71.07, 21.61 and 7.32 %, respectively. The functional groups investigation by FTIR spectroscopy exhibited distinct spectral features of CNTs and the peaks observed at 516.78 and 588.70 cm?1 correspond to the characteristic vibrations of metal-oxygen (M?O) bond that indicates the presence of CuO in the hybrid CNTs-CuO NC TF. The optical property of the CNTs?CuO NC TF with CNTs weight proportion of 0.5 % inspected through UV-Vis-NIR spectroscopy exhibited high solar absorptance and thermal emittance values of 85.9 and 4.3 %, respectively. The observed highest solar selectivity value of 19.98 suggests that the CNTs?CuO NC TF coating can be apparently used as solar selective absorber. ? 2024 Wiley-VCH GmbH.